URGENSI PERLINDUNGAN HUKUM BAGI PEGAWAI NOTARIS SEBAGAI SAKSI ATAS KESALAHAN NOTARIS DALAM PEMBUATAN AKTA OTENTIK - Solihatunnisa, Liha; Djajaputra, Gunawan (UNES Law Review, 2023)
Notary staff has a very important role in assisting the performance of a notary in providing deed-making services. Apart from being able to help the performance of a notary in carrying out his position, he must also be able to be an instrumental witness in making and formalizing notarial deeds as long as they meet the requirements stipulated in Article 40. Law on the Office of Notaries, namely witnesses who are at least 18 years old who are categorized as legal subjects who are capable of carrying out legal actions, understand the language used in the deed, can put signatures and initials, because the notary employee acts as an instrumental witness in the formalization of the deed, already entered into the realm of law which has legal consequences, so that if a notarial deed in the future occurs a problem or case, the notary employee automatically becomes involved in the problem or case. Witnesses in notary deed cases must also receive legal protection and their safety must be guaranteed in the event of a case or lawsuit in court against a deed where the status of being a witness. Even though the actions of a notary employee as an instrumental witness in the formalization of a notarial deed are included in the field of notarialism, the Law on the Position of a Notary does not provide legal protection for witnesses in the formalization of a notary deed, especially for notary employees. In the absence of provisions in the Notary Office Law regarding protection for notary employees who become instrumentair witnesses in the formalization of deeds, legal protection for notary employees who act as witnesses can only be found in provisions outside the notary office regulations.